The Contribution of Asset Optimization to Enhancing Educational Quality in Resource Management Institutions - Agustina, Evelyna; Mediaty, Mediaty; Syamsuddin, Syamsuddin (Jurnal Ekonomi, 2024)
This research aims to determine the effect of inventory, legal audit, assessment of state property, and supervision and control on optimizing asset utilization. The population in this study was all employees within the Ciliwung Cisadane River Region Center, namely 315 people. This sampling technique used purposive sampling. The primary criteria for determining the sample are 62 employees with related responsibilities and authority related to State Property. The samples in this research are 62. The types of data used in this research are primary and secondary. Data collection methods in this research are surveys and questionnaires. Data analysis in this study used multiple linear regression analysis using SPSS (Statistical Product and Service Solution) software for Windows. The research results show that inventory has a significant effect on optimizing asset utilization and has a positive relationship. Legal Audits significantly affect optimizing asset utilization and have a positive relationship. Valuation of State Property has a substantial effect on optimizing asset utilization and has a positive relationship. Supervision and Control considerably affect optimizing asset utilization and have a positive relationship.